2020
DOI: 10.1002/sctm.19-0150
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of remnant undifferentiated neural cells following human induced pluripotent stem cell-derived neural stem/progenitor cells transplantation

Abstract: Transplantation of human‐induced pluripotent stem cell‐derived neural stem/progenitor cells (hiPSC‐NS/PCs) is a promising treatment for a variety of neuropathological conditions. Although previous reports have indicated the effectiveness of hiPSC‐NS/PCs transplantation into the injured spinal cord of rodents and nonhuman primates, long‐term observation of hiPSC‐NS/PCs post‐transplantation suggested some “unsafe” differentiation‐resistant properties, resulting in disordered overgrowth. These findings suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In the preclinical study with mice, abnormal growth of the transplant was estimated from the eighth week after transplantation by deterioration of motor function and could be confirmed histologically by the 12th week [ 32 ]. Moreover, abnormal cell growth can be detected by positron emission tomography (PET) imaging by day 28 at the earliest [ 33 ]. Based on these results from animal studies, the time interval between the first and second transplantation is set to a minimum of 12 weeks.…”
Section: Methods: the Protocol Of The Clinical Studymentioning
confidence: 99%
“…In the preclinical study with mice, abnormal growth of the transplant was estimated from the eighth week after transplantation by deterioration of motor function and could be confirmed histologically by the 12th week [ 32 ]. Moreover, abnormal cell growth can be detected by positron emission tomography (PET) imaging by day 28 at the earliest [ 33 ]. Based on these results from animal studies, the time interval between the first and second transplantation is set to a minimum of 12 weeks.…”
Section: Methods: the Protocol Of The Clinical Studymentioning
confidence: 99%
“…The remnant undifferentiated NPCs showed a high expression of the 18-kDa translocator protein (TSPO), also known as the peripheral-type benzodiazepine receptor. Because the TSPO-selective radioligand [ 18 F] FEDAC is available as a clinically relevant nuclide, we proposed that the remaining NPCs after transplantation could be detected using positron emission tomography (PET) imaging [17]. When non-tumorigenic iPSC-NPCs were transplanted into central nervous system (CNS) tissue, the cells did not show uptake of the [ 18 F] FEDAC in PET imaging.…”
Section: Detection Of Tumor-like Proliferating Cells Using Positron Ementioning
confidence: 99%
“…Researchers created an in vitro selective system to ablate immature proliferating cells by introducing suicide genes into the cells [37]. In addition, by identifying and labeling undifferentiated cell markers, researchers are able to monitor remnant immature cells in vivo [38]. Moreover, recent clinical studies showed that the rejection of grafts have not been observed in patients for at least short-term period without using immunosuppression methods (Table 1).…”
Section: Applications Of Ipscs In the Regenerative Fieldmentioning
confidence: 99%